Comparative Detection of Canine Parvovirus by Differential PCR, Conventional PCR and Nested PCR tests: Detecting Antigenic Variants by Differential PCR - Sibel Hasırcıoğlu; Hatice Pelin Aslım (Turkish Journal of Agriculture: Food Science and Technology, 2022)
Canine parvovirus (CPV) is a pathogen causing hemorrhagic enteritis in puppies and mainly transmitting via feco-oral route. In this study, stool samples were collected from a total of 35 animals suspected of CPV. The samples were examined by Conventional PCR, Nested PCR and Differential PCR tests. 20 out of 35 dogs (57.1%) were detected positive by conventional PCR, 31 (88.6%) by nested PCR and 30 (85.7%) by differential PCR. CPV 2a was stated as the most common antigenic type, male animals and 0–3-month-olds had a high rate of becoming sick and vaccinated animals might also catch the disease, rarely. Accordingly, it is recommended to focus on studies providing molecular epidemiology surveillance in order to detect the existing subtypes and develop reliable diagnosis and vaccination methods.